Desiccant-coated water-sorbing heat exchanger: Weakly-coupled heat and mass transfer. (October 2017) - Tu, Y.D.; Wang, R.Z.; Hua, L.J.; Ge, T.S.; Cao, B.Y.
Graphical abstract: Featured picture: Illustration of the novel concept of temperature and humidity loosely-coupled control (THLC). Highlights: A validated mathematical model was established to analyze the performance of the solid desiccant-coated water-sorbing heat exchanger. The special features of weakly-coupled heat and mass transfer was found and a novel concept of temperature and humidity loosely-coupled control strategy was proposed for the first time. Both the outlet air temperature and humidity ratio of evaporator can be described by exponential functions of time but with different change rate constants. Abstract: Desiccant-coated, water-sorbing heat exchanger has been proposed and investigated which shows a great advantage to independently treat the sensible and latent heat load but without sacrificing compactness and comfort. Here, a theoretical and experimental study was made to investigate and predict its dynamic behaviors of heat and mass transfer in response to the step change of the operational mode switch which is essential to continuous operation but harmful to its sensible load capacity. The results show that it has a special feature of weakly-coupled heat and mass transfer, which opens up the possibility of adopting temperature and humidity loosely-coupled control strategy to independently control the temperature and humidity on a single exchanger at the same time. Both the outlet air temperature and humidity ratio of the evaporator in response to the step change of the operational mode switch can be described by two individual exponential functions of time, which indicates that the linear driving force model is possibly valid to describe the water uptake kinetics of the water-sorbing heat exchanger even if the real working conditions are non-isothermal and non-steady.